Construction of News Headlines in Influencing Public Opinion: A Study of Hypodermic Theory : A Study of Hypodermic Theory - Rizqi Fitrianti; Noerma Kurnia Fajarwati; Eka Susilawati; Endayani Endayani; Amelia Amelia (Institute Of computer Science (IOCS), 2024)
The choice of diction in news headlines is a construction to produce meaning that can influence audiences. A news headline can influence our cognition to produce behavioral changes. Audiences gain influence as a result of the concept of hypodermic or needle theory as an effect of mass communication. This theory assumes that audiences are unable to resist the messages and influences carried out by the media in a news story. The purpose of this research is to find out the extent to which the construction of a headline on the news can influence readers' opinions. So that readers are directly affected by the news message. The method used in this research is a descriptive qualitative approach from various literature reviews using the constructivism paradigm. The theory used to identify problems is the hypodermic theory. The result of this research is that audiences are actively or passively influenced by the message of the title given by a news story in the media. The headline is the first step of a message in influencing the reader's opinion